Indolestes lafaeci sp. nov. (Odonata: Lestidae) from Timor, with comparisons to related species - Seehausen, Malte (Zootaxa, 2017)
Indolestes lafaeci sp. nov. is described and illustrated (holotype male: vi.1929, Soe, South Central Timor Regency, West Timor, Indonesia, ex.-Coll. Le Moult; deposited at the Institut Royal des Sciences Naturelles de Belgique, Brussels, Belgium). Indolestes insularis comb. nov. is proposed. For comparison, illustrations of the head, synthorax, male anal appendages and genital ligula as well as of the ovipositor of I. bellax, I. gracilis and I. insularis are given.